ЛЮМИНЕСЦЕНЦИЯ МИНЕРАЛОВ ИЗ УРАНОНОСНЫХ ЩЕЛОЧНЫХ МЕТАСОМАТИТОВ - Морошкин В.В.; Рассулов В.А. (My University, 2006)
Photo-(PhL), laser- (LL), and roentgen luminescences (RL) of minerals participating in ores of the deposits connected with alkaline metasomatites were investigated for their samples from two uranium-bearing districts - Kirovogradsky (Ukrainian shield) and El'konsky (Aldan shield). It has been revealed that the previously studied violet-blue PhL of calcite from uranium ore deposits may be used as a prospecting-appraisal index for the relatively rich ore-bearing zones, e. g. for ore deposits of the above mentioned type. Another sign for these ore-zones is the intensive luminescence of Eu2+, Fe3+ and uranyl-ions adsorbed in albite, and PhL of uranyl minerals in products of the brannerite alteration. There were registered centers of Tb3+, Sm3+ and Dy3+ in PhL spectra of calcite, and the rarely met Sm3+ and Tb3+ centers in the LL spectra of albite.
Keywords: 54953537